Becas Chile Scholarship: When Bureaucracy Jeopardises Contribution: Addressing Challenges and Opportunities in the Becas Chile Postgraduate Scholarship Program - Lopez-Rios, Maria; Álvarez-Figueroa, Francisca; Montenegro Cornejo, Karla; Orlando Plaza, Daniel; Tapia, Franco; Valdés, Mary (Notas de Antropología de las Américas, 2025)
The Becas Chile scholarship programme, established to advance Chile’s scientific and cultural development through graduate studies abroad, faces critical challenges in achieving its founding objectives. Despite significant investments in human capital, the programme’s rigid return policy hinders the effective contribution of scholars into Chile’s academic and professional ecosystems, leading to inefficiencies and underutilisation of their expertise. This position paper critiques the current framework, arguing for a flexible shift. Drawing from international best practices, such as Germany’s DAAD programme and recent survey data highlighting spontaneous professional activities that could be considered contribution efforts among scholarship holders and alumni. The paper proposes comprehensive reforms. These include developing strategic reintegration plans, flexible contribution mechanisms, and retroactive policy adjustments to address systemic inequities while maximizing benefits for Chilean society. By prioritizing dynamic global collaboration over bureaucratic compliance, Becas Chile can better align with its mission to foster national development while maximising the global potential of its scholars. The proposed reforms aim to transform Becas Chile into a world-class programme, integrating global standards with localised needs to ensure equity and effectiveness in its contributions to Chile’s socio-economic advancement.